Blunted Day-Night Changes in Luteinizing Hormone Pulse Frequency in Girls With Obesity: the Potential Role of Hyperandrogenemia - Collins, Jessicah S.; Beller, Jennifer P.; Burt Solorzano, Christine; Patrie, James T.; Chang, R. Jeffrey; Marshall, John C.; McCartney, Christopher R. (The journal of clinical endocrinology and metabolism, 2014)
Context:Puberty is marked by sleep-associated changes in LH pulse frequency and amplitude. Early pubertal girls with obesity exhibit blunted day-to-night changes in LH secretion; whether this occurs in late pubertal obese girls is unknown.Objective:The objective of the study was to test two hypotheses: 1) blunted day-to-night changes in LH secretion occur in both early and late pubertal obese girls, and 2) such alterations are specifically associated with hyperandrogenemia.Design:This was a cross-sectional analysis.Setting:The study was conducted at a clinical research center.Patients or Other Participants:Twenty-seven early pubertal, premenarcheal girls (12 of whom were obese) and 63 late pubertal (postmenarcheal) girls (27 of whom were obese) participated in the study.Intervention:Blood samples were taken every 10 minutes from 7:00 pm to 7:00 am.Main Outcome Measure:Change in LH pulse frequency [LH interpulse interval (IPI)] from daytime hours (7:00 pm-11:00 pm, while awake) to nighttime hours (11:00 pm to 7:00 am, while generally asleep).Results:Both nonobese and obese postmenarcheal girls demonstrated significant day-to-night decreases in LH pulse frequency (IPI increases of 33% and 16%, respectively), but day-to-night changes were blunted in obese girls (P = .004, obese vs nonobese). Day-to-night LH pulse frequency decreased significantly in postmenarcheal obese subjects with normal T concentrations (26% IPI increase) but not in those with hyperandrogenemia. Similar differences were evident for LH pulse amplitude. Nonobese and obese early pubertal girls exhibited nonsignificant differences in day-night LH pulse frequency (day to night IPI increase of 26% vs decrease of 1%, respectively).Conclusions:Day-to-night changes in LH pulse secretion are blunted in postmenarcheal obese adolescent girls. This phenomenon may in part reflect hyperandrogenemia.